Telemedicine Challenges during COVID-19 Pandemic: A Prospective Future of Healthcare - Ranit Bag; Malabika Mondal; Soumik Mukherjee (Pharmaceutical Research: Recent Advances and Trends Vol. 7, 2024)
Aim: This study was conducted to reveal the problems of the telemedicine sector and to provide suggestions for its use in the future. Introduction: Telemedicine technologies are a form of medical care and training that can counteract the spread of a COVID-19 epidemic by eliminating direct contact of both medical workers with patients and medical workers and patients with each other. The COVID-19 pandemic was a global threat that affected the economy as well as the health system in India. The majority of rural and non-urban areas were inaccessible and did not have adequate access to all health services. Technologies like telemedicine services were important in this case. These telehealth services, which served a sizable portion of the populace, attempted to restore the health system at the lowest possible cost. Telemedicine doctors could counsel on patients’ emergency situations while lightening the load on secondary hospitals. The guidelines should be revised to address the weaknesses and establish an ongoing system of evaluation to permit future improvements in the health system. Telemedicine technologies will continue to grow and be adopted by more healthcare practitioners and patients in a wide variety of forms, and these practice guidelines will be a key factor for handling emergency health conditions in the future. Materials and Methods: It was a record-based, cross-sectional study done in the Telemedicine Center at IPGMER, Kolkata, from 1st January to 31st January 2022. Patients were interrogated by simple questionnaires over the telephone. Real-time reverse transcriptase-polymerase chain reaction (RT-PCR) for COVID-19 antibody-positive or suspected COVID-19-positive patients was included in the study. Patients related to vaccines or enquiring about other health-related problems were excluded. Results: In 92 patients, the mean age was 48.75 ± 4 and there were about equal no. of male and female patients. Among comorbidities, the number of hypertensive, chronic obstructive pulmonary disease (COPD), and diabetes mellitus were higher. The duration of symptoms is longer in these comorbid patients. Among antibiotics, azithromycin was the most prescribed. The percentage of encounters with antibiotics was much higher than the World Health Organization (WHO) standard. The percentage of drugs from the essential drug list was about the same as the WHO standard. The average consultation time was lower than 7 minutes of the WHO standard. This study showed that comorbidities like hypertension, diabetes mellitus, COPD, etc., affected the duration and severity of COVID-19 symptoms. There were overuses of antibiotics as well as other drugs more than WHO indicators but consultation time was less than WHO indicators. More patients were satisfied with this service than in previous studies. People with poor health receive health advice to improve their quality of life. Telemedicine services can reduce the risk of self-medication by prescribing medications appropriately and promptly. Conclusion: Telemedicine services can reduce the risk of self-medication by prescribing medications appropriately and promptly. There are some problems in this study, in which medications were prescribed based on symptoms of hearing loss without a physical examination. Artificial intelligence-based technologies can modify the services. Finally, by overcoming all obstacles, this service should be a part of the “triage” plan in the health of the future.